Decisions to Use Telemedicine During The COVID-19 Pandemic: The Effects of Perceived Fear, Information Quality, and Trust - Nindi Yulaikah; Yessy Artanti (Social Science Studies, 2022)
The emergency COVID-19 pandemic brings anxiety in the world and has changed customer behavior especially in the decision to use technology in the health sector. Digital health care changing consumer behavior from using conventional health services to digital. Health technology, telemedicine are designed for long-distance communication between doctor and patient, which is considered to bring effectiveness and efficiency during the COVID-19 pandemic. This research aims to examine perceived fear, information quality, and trust to use telemedicine during the COVID-19 pandemic. This research focuses on Halodoc users aged 17-45 years and uses a non-probability technique sampling. Respondents for this research were collected using an online questionnaire. Data were analyzed by the multiple linear regression method. The result showed the information quality and trust had significant effects on the decision to use M-health. However, perceived fear has no significant effect on to use of M-health.